Pemetaan Outlet Mall Menggunakan Location-Based Augmented Reality Berbasis Mobile - Chaulina Alfianti Oktavia; Agnes Nola Sekar Kinasih; Rakhmad Maulidi (Prosiding SISFOTEK, 2021)
Mall Olympic Garden is a mall located in Malang city with more than 50 outlets. The main objective of this research is to present a way to facilitate the search and navigation for a particular outlet in the mall. The method used in this research is direct observation and sampling and then use this information to build a navigation android application with augmented reality features. The application was then tested with the help of several visitors at the Mall Olympic Garden. The average of the research results shows that the respondents feel helped by this application through this research